Phytochemical, Antioxidant, Antimicrobial, Thrombolytic as well as Cytotoxic Studies on the Stem Bark of Manilkara zapota (Sapotaceae) - Noor, S.; Prodhan, A.; Zohora, F.T.; Tareq, F.S.; Ahsan, M.; Hasan, C.M.; Islam, S.N. (Asian Journal of Chemistry, 2014)
A total of seven compounds were isolated from the methanolic extract of the stem bark of Manilkara zapota (Family:Sapotaceae) and their structures were elucidated as chondrillasterol (1), stigmasterol (2), b-sitosterol (3), lupeol (4), lupenone (5), glut-5(6)-en-3b-acetate (6) and olean-12-en-3b-acetyl-11-one (7) by 1H NMR spectra and confirmed by comparison with previously reported data. Among these chondrillasterol, glut-5(6)-en-3b-acetate and olean-12-en-3b-acetyl-11-one had been isolated for the first time from this plant. Different fractions of crude methanolic extract were also studied for antioxidant, antimicrobial, thrombolytic and cytotoxic activities. The methanolic extract of stem bark of M. zapota showed the significant free radical scavenging activity with IC50 value 1 μg/mL. Antimicrobial activity was carried out against six Gram-positive and eight Gram-negative bacteria using ciprofloxacin as standard. The maximum zone of inhibition produced by methanolic extract and its aqueous fraction was found to be 13 mm against Sarcinalutea and 17 mm against Serratia species respectively.